A Novel Tangible Interaction Authoring Tool for Creating Educational Activities: Analysis of its Acceptance by Educators - Artola, Veronica; Sanz, Cecilia; Baldassarri, Sandra (IEEE transactions on learning technologies, 2023)
The creation of applications based on tangible interaction (TI applications), particularly on tabletops, is a developing area that requires the collaboration of professionals with expert knowledge in specific domains. Having an authoring tool that facilitates interdisciplinary intervention in the design and implementation of such applications is a current challenge to bring TI to different contexts. This article presents an authoring tool (named EDIT) and analyzes its acceptance by educators for creating educational activities. The novelty of the tool lies in the possibility of creating projects with a schedule of educational activities, sequenced as required for a group of students. In addition, it has specific characteristics for the educational scenario, such as the personalization of feedback and the meta-annotation of projects. Sessions were held with educators (n = 38) to analyze variables related to the Technology Acceptance Model (such as perceived usefulness and perceived ease of use) when creating TI educational activities on tabletops using the EDIT tool. The sessions were observed and recorded on video, and a Focus Group was held afterwards. During the sessions, educators gave a positive assessment in relation to using this type of tool. It was observed that, in general, they find tangible interaction valuable mostly for working with children. Finally, the results show a high acceptance obtained from the TAM and the novel features of EDIT were found to be useful.